Genetic counseling and screening of consanguineous couples and their offspring practice resource: Focused Revision. Issue 5 (26th July 2021) - Bennett, Robin L.; Malleda, Neeraja R.; Byers, Peter H.; Steiner, Robert D.; Barr, Kimberly M.
Abstract: There are no evidence‐based guidelines to inform genetic counseling for consanguineous couples and their offspring. This focused revision builds on the expert opinions from the original publication of "Genetic Counseling and Screening of Consanguineous Couples and Their Offspring, " based on a review of literature published since 2002.